Polycyclic ethers and an unexpected dearomatisation reaction during studies towards the bioactive alkaloid, perophoramidine. Issue 26 (28th June 2018) - Johnston, Craig A.; Wilkie, Ross P.; Krauss, Helmut; Neal, Andrew R.; Slawin, Alexandra M.Z.; Lebl, Tomas; Westwood, Nicholas J.
Abstract: The bioactive alkaloid natural product perophoramidine and the related family of compounds known as the communesins have inspired the synthesis community for more than a decade. Many of the elegant approaches have required the synthesis of complex intermediates that have not always reacted in the expected manner. In this study we describe a series of cyclic ether-containing precursors that were prepared during our synthetic studies towards these natural products. Attempts to open the cyclic ether ring and trap the resulting stabilised carbocation with a carbon nucleophile ultimately led to the preparation of a diallyl-substituted all carbon quaternary centre. Subsequent attempts to differentiate between the two allyl groups resulted in a relatively clean transformation to an unexpected compound. Extensive structural characterisation, including small molecule X-ray crystallography, showed that a dearomatisation reaction had occurred. Graphical abstract: Image 1